ENGLISH TEACHING IN THE DIGITAL AGE: EXPLORING THE POTENTIAL OF TELEGRAM CHANNELS AND BOTS FOR EDUCATION - Мостовая, В.И. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2024)
The use of Telegram channels and bots in English language education is an effective element of the modern learning process. The article aims to emphasize the significance of utilizing Telegram channels and bots for a personalized approach, filling knowledge gaps, and enhancing student motivation.
Keywords: digital transformation; education; Telegram; English language; educational technologies